A double-slotted microstrip rectangular 6x6 array for sub-6 GHz wireless applications - Hossain, A K M Zakir; Hossain, Fahmida; Nor, Mohd Khanapiah; Hassim, Nurulhalim (Seventh Sense Research Group, 2024)
In this article, a double-slotted microstrip rectangular 6×6 MIMO array antenna is proposed with an intention for the sub-6 GHz smartphone and wireless applications. In this proposed design, the Partial Ground Plane (PGP) technique is applied to the Single-Element Antenna (SEA) design to achieve an Ultra-Wideband (UWB) response of 1.43GHz. The design works within 3.1 to 4.53 GHz of -10 dB S-parameter bandwidth (BW). The SEA has a small dimensions of only 40 × 30 mm² and a 0.508 mm thickness. Moreover, the 6-element array aligns with 6.6-inch display smartphones by having a final dimension of 75 × 150 mm². The MIMO performance parameters of this proposed design have a good isolation of below -16.6 dB between the ports. Furthermore, the maximum Realized Gain (RG) of 5.44 dBi, and a Total antenna Efficiency (TE) of as high as 80% are achieved by simulation and also validated through measurement. Likewise, the Envelope Correlation Coefficient (ECC) of this MIMO array stays consistently below 0.004 and has a Diversity Gain (DG) of more than 9.98 throughout the entire BW. Additionally, the Specific Absorption Rate (SAR) analysis with Hand-Head phantom reveals a remarkable result of as low as 0.094 W/kg for 10g mass at port 2, whereby the value never goes higher than 0.413 W/kg at any port that ensures compliance with MIMO standards for smartphone applications